ESTIMATING THE POLLUTION RISK OF CATCHMENT BASIN IN RIVERS WITH THE FUZZY LOGIC THEORY - Khademi, Elnaz; Amazajardi, Ramin Asadpour (Gênero & Direito, 2019)
One of the most important problems associated with water is the pollution of surface and underground waters mainly due to human activities that currently threatens many of the world’s water resources. The study area of Sabalan dam basin is on Gharasu located at 30 km (air gap) in Northeast of Meshkinshahr (Ardebil province) on the northern slopes of Mount Sabalan. This study was conducted to identify, classify and manage the pollution risk of Sabalan dam. The overall objective of this study was to predict possible events and identify risk factors, potentials and risks in pollution incidents at Sabalan Dam using URSM methods and fuzzy logic in MATLAB, Fuzzycell and Arc Gis software environments. The results of the URSM method showed that the catchment basin has a pollution risk of 0.43-0.66. The results of this method and fuzzification in the MATLAB software revealed that the basin has the risk in the range of 0.16 to 0.76. Therefore, it can be concluded that using the URSM method and its integration with fuzzy logic in risk assessment can reduce the disadvantages of other methods such as ursm (alone).